2022
DOI: 10.32604/iasc.2022.019121
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-Attack Detection and Mitigation Using SVM for 5G Network

Abstract: 5G technology is widely seen as a game-changer for the IT and telecommunications sectors. Benefits expected from 5G include lower latency, higher capacity, and greater levels of bandwidth. 5G also has the potential to provide additional bandwidth in terms of AI support, further increasing the benefits to the IT and telecom sectors. There are many security threats and organizational vulnerabilities that can be exploited by fraudsters to take over or damage corporate data. This research addresses cybersecurity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The calculated throughput and intrusion detection rate are higher, while the latency, energy consumption, and packet loss rate are lower, indicating that the proposed approach has achieved better QoS. Alshunaifi et al [11] used MLP and LSTM networks for SQL injection detection. The study concluded that LSTM has excellent potential in threat intelligence detection.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated throughput and intrusion detection rate are higher, while the latency, energy consumption, and packet loss rate are lower, indicating that the proposed approach has achieved better QoS. Alshunaifi et al [11] used MLP and LSTM networks for SQL injection detection. The study concluded that LSTM has excellent potential in threat intelligence detection.…”
Section: Related Workmentioning
confidence: 99%
“…In the studies, the authors suggest that further research using other machine learning methods with multi-class data is required because previously employed methods used binary data in their studies. Another study has discussed SQLi detection using Multi-Layered Perceptron (MLP) and long short-term memory (LSTM) networks, both of which achieved 97% accuracy, with MLP having a bit higher accuracy compared to the LSTM [11]. The keyword recognition capabilities and special character detection using LSTM need improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In the formula, λ � 0.5. X (0) is the original multiscale network trafc, X (1) is the cumulative sequence of X (0) and Z (1) is the adjacent mean sequence of X (1) , so the grey Verhulst prediction model can be constructed.…”
Section: Mathematical Modeling Of Multiscale Network Trafcmentioning
confidence: 99%
“…Instant messaging software, high-defnition video transmission, and other applications relying on high-speed networks are increasingly popular, which puts forward higher requirements for the Internet transmission capacity and information carrying capacity. At this stage, the network has become an inseparable part of people's lives, and the network is an important foundation of the information society, constantly promoting economic development and social progress [1,2]. As a special time series, network trafc has the characteristics of being multiscale, nonlinear, and scale-dependent [3].…”
Section: Introductionmentioning
confidence: 99%
“…The security measures used for IoT devices, such as authentication, network security, encryption, access control, and application security, are ineffective, and their vulnerabilities are deeply rooted. Therefore, existing security methods need to be improved to ensure that the IoT ecosystem is indeed secure [18,19].…”
Section: Related Workmentioning
confidence: 99%